Exploring Scientific Identity in Teacher Education: A 20-Year Bibliometric Analysis - Fadhilah, Anita; Hernani; Mudzakir, Ahmad (Universitas Pendidikan Ganesha, 2024)
Investigating scientific identity in teacher education is essential, as teachers play a pivotal role in advancing education and facilitating the learning process. Their impact is critical to student success, particularly within structured school environments. This bibliometric study aims to analyze the scientific identity in teacher education over the past two decades. Utilizing VOSviewer, the authors mapped 541 relevant articles (7,880 citations) indexed in Scopus, published between 2004 and 2024. Qualitative analysis methods revealed an overall increase in publications, though a decline was observed from 2020 to 2024. This study highlights the significance of scientific identity in teacher education, emphasizing its role in shaping attitudes, enhancing science literacy, and facilitating effective learning. The findings suggest that future research should integrate scientific identity into curricula to address global sustainability challenges. The paradigm shift in science education during the 2010s, which emphasized broader scientific knowledge and skills, necessitates that teachers develop a clear and stable scientific identity in teaching science.